The role of national hospital associations in health system governance before and during the COVID-19 pandemic: Findings from an exploratory online survey - Bruno Meessen; Sara Perazzi (Elsevier, 2022)
Objective: Building on the premise that health authorities should govern their health systems in partnership with the full community of stakeholders, we document the contribution of national hospital associations to health policy processes, before and during the COVID-19 crisis. Methods: This research followed a rapid cross-sectional comparative design. Data were collected through an online survey targeting hospital associations. Eighteen of them shared information on their institutional profile, their areas of activity, their position and participation as policy actors before and during the COVID-19 crisis, the barriers and enablers affecting their participation and the impact of the crisis on their own financial situation. Findings: We have documented a spectrum of situations both for national policy platforms and hospital associations. In some countries, there is the ideal match of well-established associations and national participatory health policy platforms. In others, hospital associations have modest staffing and may struggle to get access to policy platforms of importance. Being a well-established and respected contributor seems to have been an enabling factor for the contribution of the hospital associations to the COVID-19 response. For most associations, the crisis has led to an increased effort to be present in the policy arena; an issue they follow closely is the negative impact of the lockdown on the hospitals' revenue. Conclusion: The growing pluralism characterizing our societies calls for the establishment of health policy platforms allowing for broader participation. Encouraging hospitals to set up their association for the latter to represent them in decision processes could be one of the components of the rebuilding of national health systems post pandemic.